Effects of dual-language programme (DLP) on the usage of English adjectives at primary school level in Malaysia - Ramli, Rashida Nasuha; Lotfie, Maskanah Mohammad; Md Zamin, Ainul Azmin (UiTM Press, 2020)
Students from selected Malaysian schools are currently learning Mathematics and Science in English under the DUAL Language Programme. They are exposed to additional hours of English compared to non-DLP ones. This paper investigates the extent to which the extra hours of English language exposure assist primary school students in grasping the morphological structures of English adjectives. The cross-linguistic differences in Malay and English could be one of the main reasons students face difficulties in acquiring English adjectives. Data were collated from two different Year 2 classes involving a DLP and a non-DLP group. Vocabulary Size Test (VST) measured the use of base form of adjectives while Comparative Adjective TEST were used for the comparative ones. Test scores were analysed to gauge the possible significant difference between the control and the experimental groups. The findings reveal that the mean scores for DLP group are not significantly higher than non-DLP group for both tests.